2021
DOI: 10.21037/apm-21-614
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and risk factors of mechanical thrombectomy for the treatment of vertebrobasilar artery occlusion: a single center study

Abstract: Background: The mortality of acute ischemic stroke patients caused by vertebrobasilar artery occlusion (VBAO) is high and mechanical thrombectomy has gradually become a promising treatment for acute ischemic stroke. This study analyzed the efficacy of mechanical thrombectomy and the risk factors associated with poor outcomes in VBAO patients caused by severe local atherosclerotic stenosis.Methods: This retrospective study enrolled patients with acute ischemic stroke caused by VBAO between March 1, 2016 and Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Consistent with previous studies, this study confirmed that the pc‐ASPECTS score was correlated with MT outcome (Alemseged et al., 2019 ; Sang et al., 2021 ; Wu et al., 2021 ; Yao et al., 2021 ). A previous study with a large sample size revealed that patients with pc‐ASPECTS ≥5 could benefit from MT (Sang et al., 2021 ), while another small sample study showed pc‐ASPECTS ≥8 was the boundary (Alemseged et al., 2019 ; Fabritius et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies, this study confirmed that the pc‐ASPECTS score was correlated with MT outcome (Alemseged et al., 2019 ; Sang et al., 2021 ; Wu et al., 2021 ; Yao et al., 2021 ). A previous study with a large sample size revealed that patients with pc‐ASPECTS ≥5 could benefit from MT (Sang et al., 2021 ), while another small sample study showed pc‐ASPECTS ≥8 was the boundary (Alemseged et al., 2019 ; Fabritius et al., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…So far, several studies have evaluated the prognostic factors of MT in BAO. They all used multivariable logistical regression models to ascertain the potential predictors (Alexandre et al., 2021 ; Bouslama et al., 2017 ; Diprose et al., 2020 ; Fabritius et al., 2021 ; Guenego et al., 2021 ; Kwak & Park, 2020 ; Mokin et al., 2016 ; Sang et al., 2021 ; Wu et al., 2021 ; Wu, Xu et al., 2021 ; Yao et al., 2021 ). In this study, we constructed separate pre‐ and postoperative nomogram models to conduct a comprehensive evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, age and the NIHSS were recognized to be a predictor of prognosis in BAO stroke (3,18). As shown in Table 2, the higher NIHSS on admission was significantly associated with a higher rate of futile recanalization in the present study.…”
Section: Discussionsupporting
confidence: 56%